The People Acceptance of The Red Rose (Rosa hybrida L.) Flowers Extract as Lipsticks Dye - Ambarwati, Neneng Siti Silfi; Armandari, Mari Okatini; Triraharja, Shirley Gemilang (Fakultas Teknik Universitas Negeri Malang, 2020)
This study aimed to determine the people acceptance to various red rose extract in 5 percent,7 percent, and 9 percent composition on lipsticks. The panellists were women aged between 20-25 years old as college student and employees. The total of the panellists were 30 people who lived in Tangerang and Jakarta. The extract was made using the maceration method with a water solvent. Hedonic test with observation sheet was used to score the people acceptance. There were two aspects in this study, the flavour, and the colour. Friedman test and Tukey test were used to analyze the data result. The result showed that panellists most preferred the 7 percent additional extract for two aspects. The conclusion was the addition 7 percent of Rosa hybrida flowers extract as lipsticks dye is the most accepted by the people either in colour and flavour